Strategic Human Resource Development for Emerging Technologies: A Scoping Review in ICT, Robotics, Data Science, and CPS - Leonard Chukwualuka Nnadi; Dake Ding; Ebubechukwu Delight Godwin-Ojukwu; Yutaka Watanobe; Keitaro Naruse (IEEE Access)
The rapid advancement of ICT, robotics, data science, and cyber-physical systems (CPS) has intensified the need for agile, future-ready human resource development (HRD) strategies. This scoping review explores current HRD practices, challenges, and opportunities across these technological domains. Guided by the PRISMA-ScR framework, 791 records were initially retrieved from four databases, with 43 peer-reviewed publications ultimately included following a rigorous screening process. Thematic analysis revealed a strong emphasis on digital and AI literacy, interdisciplinary training, and the adoption of immersive technologies such as virtual reality and AI-driven competency tracking systems. Persistent gaps, including misalignment between academic training and industry needs, a lack of scalable HRD models, and underdeveloped policy frameworks. Statistical comparisons revealed no significant differences across fields, indicating the cross-cutting relevance of the identified strategies. The findings underscore the need for structured, empirically grounded, and industry-integrated HRD approaches to prepare the workforce for the demands of the Fourth Industrial Revolution.